HbTGA1, a TGA Transcription Factor From Hevea brasiliensis, Regulates the Expression of Multiple Natural Rubber Biosynthesis Genes - Guo, Dong; Li, Hui-Liang; Zhu, Jia-Hong; Wang, Ying; Peng, Shi-Qing (Frontiers in Plant Science, 2022)
The TGA transcription factors are known to modulate the biosynthesis of secondary metabolites in plants. However, their regulatory function in natural rubber (NR) biosynthesis was not revealed in the rubber tree (Hevea brasiliensis). Here, 14 genes encoding TGA transcription factors (name HbTGA1-HbTGA14) were identified in the rubber tree. HbTGAs were differentially expressed in different tissues. HbTGA1 was expressed at its highest level in latex. We found specific in vitro and in vivo binding of the HbTGA1 protein with promoters of multiple NR biosynthesis genes (HbHMGS2, HbHMGR2, HbCPT6, HbCPT8, and HbSRPP2). The activation of the promoters of HbHMGS2 and HbCPT6 was significantly suppressed by HbTGA1, while the activities of promoters of HbHMGR2, HbCPT8, and HbSRPP2 were increased by HbTGA1. The promoter activities of HbHMGS2, HbHMGR2, HbCPT6, HbCPT8, and HbSRPP2 were significantly increased by HbTGA1 under jasmonate stress, while the promoter activities of HbHMGS2, HbHMGR2, HbCPT6, HbCPT8, and HbSRPP2 were also significantly increased by HbTGA1 under salicylic acid stress. The present study provides insights into the role of TGA transcription factors in regulating the expression of NR biosynthesis genes from Hevea brasiliensis.